Simulasi Numerik Osilator Harmonis - Edi Widodo, Catur (BERKALA FISIKA, 2007)
A program for explain movement the harmonis oscillator have been done with Python programming language version 4.2. Program was simulated simple harmonic oscillator and damped harmonis oscillator.Program was constuct by mean finite difference equation in object oriented programming Python. First, object simulation is simple harmonic motion consist spring and mass slides on a frictionless horizontal surface. Second, object simulation is damped harmonic motion consist spring, mass and piston. The result of simulation indicated that the frequency osilation depend with force constant of the spring and mass, and damped depend damping ratio and mass. Â